Innenansicht des Eingangs des Hauses der Beiers in Sydney (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Africa; Artists; Interior decoration; Painting; Photographs; Sydney; Art Collector; Art Collecting